Phacoemulsification versus small incision cataract surgery (SICS): which one is a better surgical option for immature cataract in developing countries? (Nepalese Journal of Ophthalmology, 2010)
Background: Several studies have shown comparable visual outcomes of SICS and phacoemulsification (Gogate et al 2007, Ruit et al 2007). Objective: To compare the safety and efficacy of different types of surgical procedures (phacoemulsification versus SICS) for cataract surgery in immature cataract. Material and methods: A prospective randomized controlled trial was carried out involving 93 and 89 patients with immature senile cataract selected for phacoemulsification and SICS respectively. Statistics: Mean values with standard deviations were calculated. P value of less than 0.05 was considered significant. Results: There was no difference between the groups in terms of gender, age and pre-operative visual acuity (p = 0.09). In phacoemulsification group (n=93) more than two thirds and in SICS group (n=89) more than three quarters of the patients had good visual outcome (6/6-6/18) on first postoperative day (p=0.065). Poor outcome (